A randomized controlled evaluation of alveolar ridge preservation following tooth extraction using deproteinized bovine bone mineral and demineralized freeze-dried bone allograft - Rokhsareh Sadeghi; Maryam Babaei; S Asghar Miremadi; Fatemeh Mashadi Abbas (Wolters Kluwer Medknow Publications, 2016)
Background: Alveolar ridge preservation could be performed immediately following tooth extraction to limit dimensional changes of alveolar process due to bone resorption. The aim of this study was to compare the clinical and histologic outcomes of socket preservation using two different graft materials; deproteinized bovine bone mineral (DBBM) and demineralized freeze-dried bone allograft (DFDBA) with absorbable collagen membrane. Materials and Methods: Twenty extraction sockets in 20 patients were randomly divided into 2 treatment groups: 10 sockets were augmented with DBBM and collagen membrane whereas 10 sockets were filled with DFDBA and covered by collagen membrane. Primary closure was achieved over extraction sockets by flap advancement. Horizontal and vertical ridge dimensional changes were assessed at baseline and after 4-6 months at the time of implant placement. For histological and histomorphometrical analysis, bone samples were harvested from the augmented sites with trephine during implant surgery. All data were analyzed using SPSS version 18 (α=0.05). Results: Clinical measurements revealed that average horizontal reduction was 2.3 ± 0.64 mm for DFDBA and 2.26 ± 0.51 mm for DBBM. Mean vertical ridge resorption at buccal side was 1.29 ± 0.68 mm for DFDBA and 1.1 ± 0.17 mm for DBBM. Moreover, mean vertical ridge reduction at lingual site was 0.41 ± 0.38 mm and 0.35 ± 0.34 mm for DFDBA and DBBM, respectively. No significant differences were seen between two groups in any of those clinical parameters. Histologic analysis showed statistically significant more new bone deposition for DFDBA compared to DBBM (34.49 ± 3.19 vs. 18.76 ± 3.54) (P < 0.01). Residual graft particles were identified significantly more in DBBM (12.77 ± 1.85) than DFDBA (6.06 ± 1.02). Conclusion: Based on the findings of this study, both materials have positive effect on alveolar ridge preservation after tooth extraction, but there was more new bone formation and less residual graft particles in DFDBA group than in DBBM group.